Review on the Formulation, Existing Problems, and Practical Effects of Fitness Exercise Prescriptions for People With Intellectual Disabilities - Yan, Zengyin; Yan, Pingping; Qin, Chunli; Luo, Jiong (Frontiers in Public Health, 2022)
Compared with normal people, patients with mental retardation have poor cardiopulmonary and muscle fitness levels, and their daily physical activity generally can not reach the "guideline recommended amount", which increases the risk of obesity and cardiovascular disease in this group. From the perspective of six elements of exercise prescription (frequency, intensity, time, form of exercise, amount of exercise and progressive rate), this paper systematically reviews the current situation of the formulation and implementation of exercise prescription for patients with Intellectual Disabilities. The results show that the design idea of aerobic fitness exercise prescription for patients with intellectual impairment basically follows the six element paradigm, but the insufficient recommended amount of each element is a common problem; In the design of muscle fitness exercise prescription, due to the differences of different exercise forms, the description of the six elements is very inconsistent. Although most prescription execution effects show that it is beneficial to improve cardiopulmonary and muscle fitness, there is a great debate on whether it is beneficial to improve body composition; People with intellectual disabilities are highly heterogeneous groups. In the initial stage of exercise intervention, the elements of exercise prescription need to be adjusted individually in order to obtain sustainable positive benefits.